Reconfiguration of brain-wide neural activity after early life adversity - Taylor W. Uselman; Russell E. Jacobs; Elaine L. Bearer (Proceedings of the National Academy of Sciences, 2025)
Early life adversity (ELA) predisposes individuals to physical and mental disorders lifelong. How ELA affects brain functions, leading to these vulnerabilities, is a mystery. To understand ELA’s impacts, investigations into neural activity affected by ELA must go beyond localized areas toward simultaneous recordings from multiple widely distributed regions over time. Such studies will expose relative activity between regions and discover shifts in regional activity in response to different experiences. Here, we performed longitudinal manganese-enhanced MRI (MEMRI) to measure degrees of brain-wide neural activity in ELA-exposed mice across a series of experiences in adulthood. To ascertain whether ELA resulted in atypical brain activity, results were compared to those of the standard mouse (Std). MEMRI captured activity in the freely moving home cage condition, and short- and long-term after exposure to TMT, a naturalistic predator threat. Images were normalized and aligned then analyzed with statistical mapping and automated segmentation. We found that neural activity in the home cage was greater in ELA compared to Std in multiple striatal-pallidal and hypothalamic regions. Upon acute threat, neural activity in Std increased in these regions to become more similar to that in ELA, while new hyperactive responses in ELA emerged in the midbrain and hindbrain. Nine days after acute threat, heightened neural activity in ELA persisted within locus coeruleus and increased within the posterior amygdala, ventral hippocampus, and dorsomedial and ventromedial hypothalamus. These results reveal functional imbalances that arise between multiple brain-systems after ELA, which are dependent upon context and cumulative experiences into adulthood.